Computed tomography provides enhanced techniques for longitudinal monitoring of progressive intracranial volume loss associated with regional neurodegeneration in ovine neuronal ceroid lipofuscinoses. Issue 9 (23rd August 2018) - Russell, Katharina N.; Mitchell, Nadia L.; Anderson, Nigel G.; Bunt, Craig R.; Wellby, Martin P.; Melzer, Tracy R.; Barrell, Graham K.; Palmer, David N.
Abstract: Introduction: The neuronal ceroid lipofuscinoses (NCLs; Batten disease) are a group of fatal neurodegenerative lysosomal storage diseases of children caused by various mutations in a range of genes. Forms associated with mutations in two of these, CLN5 and CLN6, are being investigated in well‐established sheep models. Brain atrophy leading to psychomotor degeneration is among the defining features, as is regional progressive ossification of the inner cranium. Ongoing viral‐mediated gene therapy trials in these sheep are yielding encouraging results. In vivo assessment of brain atrophy is integral to the longitudinal monitoring of individual animals and provides robust data for translation to treatments for humans. Methods: Computed tomography (CT)‐based three‐dimensional reconstruction of the intracranial volume (ICV) over time reflects the progression of cortical brain atrophy, verifying the use of ICV measurements as a surrogate measure for brain size in ovine NCL. Results: ICVs of NCL‐affected sheep increase for the first few months, but then decline progressively between 5 and 13 months in CLN5 −/− sheep and 11–15 months in CLN6 −/− sheep. Cerebral ventricular volumes are also increased in affected animals. To facilitate ICV measures, the radiodensities of ovine brain tissue and cerebrospinal fluid were identified. Ovine brain tissue exhibited a Hounsfield unit (HU) range of (24; 56) and cerebrospinal fluid a HU range of (−12; 23). Conclusions: Computed tomography scanning and reconstruction verify that brain atrophy ovine CLN5 NCL originates in the occipital lobes with subsequent propagation throughout the whole cortex and these regional differences are reflected in the ICV loss. Abstract : Neuroimaging is a fast developing field for monitoring of neurodegeneration. Longitudinal CT scanning allows the assessment of disease progression and therapeutic efficacy for fast, reliable, and cost‐effective monitoring of neurodegeneration in ovine NCL. The relationship between brain atrophy and intracranial volume is poorly described in most species, and there are conflicting reports in the pathology of many human brain wasting diseases, where most observations are based on postmortem findings.